Energy Independence and Energy Efficiency of Populated Areas in the System of Management - YASNOLOB, Ilona; GORB, Oleg; KOZACHENKO, Yuliia; KALIAN, Oleksandr; BOROVYK, Tetyana; ZAHREBELNA, Iryna (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The idea of the essence of notions “energy independence” and “energy efficiency” was extended in the article taking into account the promising directions of developing energy saving, ensuring the harmonious system development. The energy policy in the populated localities of European countries was analyzed in the article and also their practical experience concerning the questions of energy independence and energy efficiency was studied. Special attention was paid to the Polish experience, because the country has the greatest number of energy independent populated localities among other European countries. The European experience of energy policy enabled to reveal economic, ecological, and social levers of forming and developing energy independence and energy efficiency of populated localities, forming the system of their management. The necessity of introducing consolidated state policy as to raising energy independence and energy efficiency of populated localities was proven, their priority directions and assistance in introducing the corresponding projects in the populated localities of Ukraine were determined. The necessity and peculiarities of energy management system for the need of project management in energy independence and energy efficiency of populated localities were investigated. Practical recommendations as to optimizing the management system of energy independence and energy efficiency of populated localities in Ukraine were developed